The Concept of Automatic Transport System Utilizing Weight Sensor - Yurni Oktarina; Tresna Dewi; Pola Risma (Universitas Sriwijaya, 2020)
The current pandemic situation insists that people find a way to create a physical distance, limiting the number of people in a closed room. The human need for commuting has led to the idea of an automatic transport system that can transport people and goods without the assistance of a driver. This idea can lead to a new